Examining consumer behavior using social media instagram in marketing 4.0 era based on customer path 5a - Ni Putu Ayu Cintya Dewi; Ida Bagus Raka Suardana (Journal of Business on Hospitality and Tourism, 2021)
The  purpose  of this  study was to  determine  the consumer  behavior of Instagram  users in Marketing 4.0 based on Customer Path 5A. Data collection techniques used observation and in- depth interview , with health protocols implemantation in New Normal. Stages in data analysis include data reduction (data reduction), presenting data (data display) and drawing conclusions and verification (conclusion drawing / verification). Based on the results of research conducted on four  NSB Beauty Studio customers who  use social media  Instagram,  the conclusion  of consumer purchasing decisions for NSB Beauty Studio service have basically through all stages of Customer Path 5A, starting from problem recognition to post-purchase behavior about Aware, Appeal, Ask, Act, and Advocate. All informants also said that Instagram helped them get to aware and make purchases of the NSB Beauty Studio brand.